2020
DOI: 10.3390/vaccines8030488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inactivated Influenza Vaccines Used in the Russian National Immunization Program

Abstract: Background: today’s standard quality control methods used to control the protein composition of inactivated influenza vaccines only take into account a few key reference components. They do not allow for thorough characterization of protein compositions. As a result, observation of unpredictable variations in major viral constituents and admixtures of cellular proteins within manufactured vaccines that may seriously influence the immunogenicity and safety of such vaccines has become a pressing issue in vaccino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…It is most likely that the essential difference in the IgG1/IgG2a ratios measured upon BALB/c vaccination with various IIVs is associated with the differences in their protein compositions, which we demonstrated earlier using label-free quantitative mass spectrometry [ 44 ]. That study manifested that the IIVs showed interpretable results only with respect to the abundance of the major antigen proteins, HA and NA, while there was a fairly wide range of data for the core proteins present in minor proportion within the investigated IIVs.…”
Section: Discussionmentioning
confidence: 91%
“…It is most likely that the essential difference in the IgG1/IgG2a ratios measured upon BALB/c vaccination with various IIVs is associated with the differences in their protein compositions, which we demonstrated earlier using label-free quantitative mass spectrometry [ 44 ]. That study manifested that the IIVs showed interpretable results only with respect to the abundance of the major antigen proteins, HA and NA, while there was a fairly wide range of data for the core proteins present in minor proportion within the investigated IIVs.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the presence of protein aggregation in a vaccine product can affect the stability and efficacy of the vaccine [ 172 ]. These aggregates can be caused by removing the splitting agent (surfactant) in the manufacturing of split-virus influenza vaccines [ 180 ]. In addition to EM and light scattering, UV−Vis absorption spectroscopy and fluorescence emission spectroscopy are reliable techniques in identifying protein aggregations [ 89 , 172 ].…”
Section: Characterization Of Vaccine Productsmentioning
confidence: 99%
“…Moreover, in split-virus vaccines, surfactant type, incubation time, virus concentration, surfactant concentration, and virus split ratio are other factors that could affect a vaccine’s stability. For example, aggregation may present after diluting or removal of the surfactant, so the remaining surfactant concentration should be monitored by optimizing the number of filtering steps to maintain vaccine stability and efficacy [ 180 ].…”
Section: Characterization Of Vaccine Productsmentioning
confidence: 99%
“…In future, our IP-targeted proteomics assays could be utilized widely to improve serological testing for numerous infectious diseases, such as HIV, hepatitis and influenza 67 , and evaluate quality and efficiency of vaccines 68 . With its nearly absolute analytical selectivity, mass spectrometry assays could serve as independent tools to evaluate diagnostic specificity of the existing serological tests, and select combinations of antigens and antibody subclasses which provide the highest diagnostic specificity.…”
Section: Ighg1_humanmentioning
confidence: 99%